Acculturation, Christian religiosity, and psychological and marital well-being among the European wives of Arabs in Israel - Abu-Rayya, Hisham Motkal (Mental health, religion & culture, 2007)
This study represents an attempt to understand the psychological and marital well-being of spouses in mixed-ethnic or faith marriages in terms of the acculturation styles that spouses adopt in adapting to a new cultural environment. A total of 156 Western and Eastern European women with an average age of 38.79 (SD = 7.05; range = 23-53) married to Israeli Arabs participated in this study. Study findings revealed that women who adopted integration or assimilation styles of acculturation achieved the highest levels of self-esteem, positive affect, marital satisfaction, and marital intimacy by statistically significant degrees. In comparison, wives who adopted a separation style achieved intermediate degrees of psychological and marital well-being, and those classed as adopting a marginalization style scored the lowest degrees of well-being. The study found also that the Christian religiosity of the wives was positively statistically significantly related to self-esteem and positive affect, and negatively correlated with negative affect, marital satisfaction, and marital intimacy. Wives from the integration or assimilation styles of acculturation recorded statistically significantly the lowest degrees of Christian religiosity, while wives sorted into the separation or marginalization styles recorded the highest degrees.